Reproducibility measurements of three methods for calculating in vivo MR‐based knee kinematics. Issue 2 (27th December 2014) - Lansdown, Drew A.; Zaid, Musa; Pedoia, Valentina; Subburaj, Karupppasamy; Souza, Richard; Benjamin, C.; Li, Xiaojuan
<x xml:space="preserve">Abstract</x> Purpose To describe three quantification methods for magnetic resonance imaging (MRI)‐based knee kinematic evaluation and to report on the reproducibility of these algorithms. Materials and Methods T 2‐weighted, fast‐spin echo images were obtained of the bilateral knees in six healthy volunteers. Scans were repeated for each knee after repositioning to evaluate protocol reproducibility. Semiautomatic segmentation defined regions of interest for the tibia and femur. The posterior femoral condyles and diaphyseal axes were defined using the previously defined tibia and femur. All segmentation was performed twice to evaluate segmentation reliability. Anterior tibial translation (ATT) and internal tibial rotation (ITR) were calculated using three methods: a tibial‐based registration system, a combined tibiofemoral‐based registration method with all manual segmentation, and a combined tibiofemoral‐based registration method with automatic definition of condyles and axes. Intraclass correlation coefficients and standard deviations across multiple measures were determined. Results Reproducibility of segmentation was excellent (ATT = 0.98; ITR = 0.99) for both combined methods. ATT and ITR measurements were also reproducible across multiple scans in the combined registration measurements with manual (ATT = 0.94; ITR = 0.94) or automatic (ATT = 0.95; ITR = 0.94) condyles and axes. Conclusion The combined tibiofemoral registration with automatic definition of the posterior femoral condyle and diaphyseal axes allows for improved knee kinematics quantification with excellent in vivo reproducibility. J. Magn. Reson. Imaging 2015;42:533–538.